Bankruptcy Risk and Optimal Capital Structure - CASTANIAS, RICHARD (Journal of Finance, 1983)
ABSTRACT This study finds shortcomings in empirical tests of the capital structure irrelevance hypothesis. The alternative hypothesis is that firms choose value maximizing mixes of debt and equity on account of bankruptcy costs and the tax deductibility of interest payments. Based upon the cross‐sectional implications of the tax shelter‐bankruptcy cost hypothesis, an alternative test of the irrelevance hypothesis is performed. The test examines the relationship between failure rates and leverage ratios for 36 lines of business. The results are inconsistent with the irrelevance hypothesis.